Peculiarities of COVID-19 infection among hospitalized patients in the city hospital of Moscow during the 6th wave of the pandemic - A. R. Askarov; A. L. Vertkin; M. A. Rudnitskaya; E. A. Zinina; M. D. Akaeva; V. Sh. Abdurashitova; V. A. Shkurenko; A. Y. Zayneeva; Zh. S. Shuminova (Лечащий Врач)
Objective. We studied risk factors of severe COVID-19, comorbid and concomitant diseases, structure of mortality in patients during the 6th wave of the pandemic who died in the hospital.Materials and methods. The study included 220 patients with coronavirus pneumonia.Results. The majority of patients with coronavirus pneumonia who died in a hospital had pneumonia (90,0%). At the same time, moderate lung damage prevailed – pneumonia with stage CT-1 (34,5%) and CT-2 (30,5%), less often – severe pneumonia (stage CT – 3-4 (28.4%)). Laboratory verification of the SARS-CoV-2 virus was confirmed in the vast majority of cases (97,5 %). A high frequency of comorbid diseases and underlying pathology was found in deceased patients with viral pneumonia: arterial hypertension (92,7%), cerebrovascular disease (87,3%), coronary artery disease (93,2%), chronic kidney disease (80,5%), peripheral arterial diseases (47,3%), type 2 diabetes mellitus (type 2 diabetes) and atrial fibrillation – in every third patient (36,4% and 34,1%), and one in five is obese (20,0%). Acute respiratory distress syndrome (68,6%) and much less often – stroke (18,2%), acute myocardial infarction (6,4%) and pulmonary embolism (6,8%) were the main causes of death in patients with SARS-CoV-2 pneumonia. In patients with fatal pneumonia caused by SARS-CoV-2, there is a high frequency of comorbid conditions and risk factors leading to a severe course of the disease: hypertension, coronary artery disease, severe chronic heart failure, advanced age (> 75 years), chronic kidney disease stages C3-C5, peripheral arterial diseases, obesity and type 2 diabetes. Among the deceased women with coronavirus pneumonia COVID-19, such cardiovascular risk factors as age > 75 years, type 2 diabetes, CHF stage 2 (A and B), obesity of 2-3 degrees, chronic microcytic anemia prevailed; among the dead men – smoking and chronic obstructive pulmonary disease, atrial fibrillation, severe chronic heart failure.